Pokemon book of evolutions the official guide to Pokemon transformations! - Andreou, Katherine (New York, NY DK Publishing, 2024)
A guide to Pokemon transformations, discussing ways Pokemon can evolve and the mysterious items that help them.
All about evolution -- Epic evolutions -- Evolution power-ups.
Subtitle from front cover
114157
Keywords: Pokemon (Fictitious characters) -- Juvenile literature; Pokemon (Game) -- Juvenile literature; handbooks; Handbooks and manuals